The Role of Duplex Ultrasound and Flow/Pressure Ratio in Predicting Invasive Treatment for High Venous Pressure in Patients Undergoing Hemodialysis - Foong-Fah Leong; Wen-Chin Lee; Hwee-Yeong Ng; Po-Yen Kuo; Chien-Te Lee; Chung-Ming Fu (Medicina)
Background and Objectives: Vascular access complications, particularly high venous pressure, pose significant challenges for hemodialysis patients undergoing hemodialysis. Limited research has focused on identifying predictive factors for invasive treatment. This study aimed to identify patients who might benefit from frequent monitoring and conservative management based on duplex ultrasound (DUS) evaluation. Materials and Methods: This retrospective study included 72 hemodialysis patients with high venous pressure who underwent DUS. Patients were divided into conservative (n = 26) and invasive treatment groups (n = 46). Key factors such as flow/pressure ratio, blood flow, and venous pressure were analyzed. Logistic regression was used to identify risk factors for invasive treatment, while receiver operating characteristic (ROC) analysis was performed to establish the optimal cutoff for the flow/pressure ratio. Results: Three months after the DUS, 3.85% of the conservative group experienced access failure, compared to 71.7% in the invasive group. The flow/pressure ratio was significantly lower in the invasive group (1.28 ± 0.26 vs. 1.47 ± 0.23, p < 0.05). A higher flow/pressure ratio (OR: 0.063, 95% CI: 0.004–0.932, p = 0.044) and the presence of tortuous veins (OR: 0.080, 95% CI: 0.007–0.897, p = 0.0405) were associated with a lower risk of invasive treatment. ROC analysis showed a flow/pressure ratio cutoff of 1.38 (AUC: 0.706, p = 0.004). Conclusions: Duplex ultrasound plays a crucial role in evaluating arterio-venous access in patients with high venous pressure. It provides a non-invasive assessment of vascular complications, helping avoid unnecessary invasive procedures. The flow/pressure ratio is significantly associated with the risk of invasive treatment, providing a valuable threshold for assessing risk and guiding clinical decision-making to optimize treatment strategies.